HUBUNGAN STATUS GIZI DAN STATUS HIDRASI DENGAN PRODUKTIVITAS KERJA PEGAWAI PUSKESMAS - Nasywa Noor Wulandari; Lie Tanu Merijanti (Fakultas Kedokteran Universitas Trisakti, 2025)
Background. Human resources (HR) is a critical element in the success of a company, as HR plays the role of both planner and executor. The quality of HR can be evaluated through employee productivity, which is influenced by various factors, including health, nutritional status, and hydration status. This study aims to assess whether there is a relationship between nutritional status and hydration status with work productivity. Method. An analytical observational study with a cross-sectional design was conducted at a community health center in East jakarta from September to November 2024. Data was collected from 151 employees who met the inclusion adn exclusion criteria, using a work productivity questionnaire that had been tested for validity and reliability. Nutritional status was measured through Body Mass Index (BMI), and hydration status was assessed through urine examination. Data analysisi was performed using the Spearman Rank Correlation and Chi-Square tests, with ethical approval from the Ethics Committee of the Faculty of Medicine, Trisakti University. Results. There was no relationship between nutrtional status and work productivity (p=0,578), dan dno realtionship between hydration status and work productivity(p=0,578). Conclusion. There is no relationship between nutritional and hydration status with work productivity.